Influence of Granulometry of the Small Aggregate on the Permeability of Wall Cement Coating - Mesquita, Kaylla Gomes; Liotto, Pedro Felix; Amorim, Fabrício Rodrigues; Santarém, Sara dos Santos; Alencar, David Barbosa de (International Journal of Advanced Engineering Research and Science, 2019)
The performance of the vertical sealing elements is determined by the level of protection to which they are subjected. Construction processes are changing and cementitious coatings are increasingly taking place among current construction options. On the other hand, the weather has its increasingly aggressive and more evident incidence. The performance standard sets the guidelines for seal manufacturers to meet expected quality standards. Given the above comes the importance of evaluating the best particle size composition to obtain the ideal mortar manufacture. Water transport mechanisms are the actors in this permeability process with the effective participation of diffusion and capillarity. The present study proposes observations about the water absorption of cementitious coatings manufactured with three sand granulometry (fine aggregate). The mixture containing the fine sand obtained the lowest absorption while the mixture with the highest grain size presented the highest absorption and the highest flow rates.